2014
DOI: 10.1111/ppa.12286
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the responses of melon accessions to fusarium root and stem rot and their colonization by Fusarium oxysporum f. sp. radicis‐cucumerinum

Abstract: Fusarium root and stem rot caused by the fungus Fusarium oxysporum f. sp. radiciscucumerinum is a major disease in greenhouse cucumbers. Over the past decade, the disease has been documented in melon greenhouses in Greece, and recently it has been sporadically recorded in greenhouse melons in Israel. Variations in disease response were found among 41 melon accessions artificially inoculated with the pathogen: 10 accessions were highly susceptible (90-100% mortality), 23 exhibited an intermediate response (20-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…In contrast to Forc016_HCT#1, Fom-derived HCT strains did not cause disease on cucumber Fo was delayed compared to colonization of susceptible plants, and only the lower hypocotyl was colonized (Zvirin et al, 2010) or only root xylem vessels were colonized (Li et al, 2014). In other studies, colonization of xylem vessels of resistant plant roots by Fo was not observed (Cohen et al, 2015;Upasani et al, 2016). In the present study, colonization of the hypocotyl of cucumber and watermelon plants by Fom005_GFP was also not observed, suggesting strong defence responses of nonhosts cucumber and watermelon at the root-stem transition.…”
Section: F I G U R Ementioning
confidence: 77%
See 1 more Smart Citation
“…In contrast to Forc016_HCT#1, Fom-derived HCT strains did not cause disease on cucumber Fo was delayed compared to colonization of susceptible plants, and only the lower hypocotyl was colonized (Zvirin et al, 2010) or only root xylem vessels were colonized (Li et al, 2014). In other studies, colonization of xylem vessels of resistant plant roots by Fo was not observed (Cohen et al, 2015;Upasani et al, 2016). In the present study, colonization of the hypocotyl of cucumber and watermelon plants by Fom005_GFP was also not observed, suggesting strong defence responses of nonhosts cucumber and watermelon at the root-stem transition.…”
Section: F I G U R Ementioning
confidence: 77%
“…conglutinans (Li et al, 2014), f. sp. radicis-cucumerinum (Cohen et al, 2015), f. sp. phaseoli (Niño-Sánchez et al, 2015;Garces-Fiallos et al, 2017), f. sp.…”
mentioning
confidence: 99%
“…Similar results have recently been reported for the interaction Fusarium oxysporum f. sp. radicis ‐ cucumerinum– melon (Cohen et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…El hongo FOM es un habitante del suelo que infecta a las plantas penetrando de forma directa o por heridas de las raíces de donde se extiende hasta el xilema; provocando marchitamiento y muerte, además de persistir en el suelo debido a la producción de clamidosporas (Agrios 2005). El control genético de esta enfermedad es el método más estudiado, se han determinado los mecanismos de respuesta de defensa constitutiva o inducida de genotipos de melón a través de observaciones microscópicas, donde se observa el comportamiento de Fusarium en el xilema (Cohen et al 2015). Para evaluar materiales genéticos por métodos moleculares van Dam et al 2017diseñaron 18 pares de cebadores de PCR, con base a genes efectores candidatos, que discriminan entre siete formas especiales que afectan a cucurbitáceas, lo que permite reconocer los genotipos hospederos de cada una de ellas.…”
Section: Introductionunclassified